Factors Influencing the Occurrence of Chronic Energy Deficiency in High-Risk Pregnant Women - Eka Wira Adesty, Riana; Anggadita, Tania; Damayanti, Rini; Tunggal Mutika, Winnie (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Pregnant women suffering from CED are at risk of sudden maternal death in the perinatal period or at risk of giving birth to a low birth weight (LBW) baby (Pamangin, 2024) Objective : To find out the factors that influence the occurrence of chronic energy deficiency in pregnant women Research Methods/ Implementation Methods : A literature review using two databases namely Google Scholar and Garuda with keywords "pregnant women", "chronic energy deficiency", "high risk", and "influencing factors". Results : Twenty-five journals, fifteen were significant with knowledge, three journals were significant with hb history, four journals were substantial with age, three journals were significant with parity, two journals were significant with pregnancy spacing, one journal was significant with diet, one journal was significant with body mass index (BMI), two journals were significant with education in high-risk pregnant women, especially with Chronic Energy Deficiency (CED). Conclusion/Lesson Learned : Knowledge, blood pressure history, age, parity, parity spacing, diet, BMI, and education play an important role in maintaining the health of high-risk pregnant women, especially those with chronic energy deficiency (CED). Structured interventions that include education, antenatal care, and supplemental feeding may be an effective preventive measure to prevent high-risk pregnancies in pregnant women, especially pregnant women with Chronic Energy Deficiency (CED).